Management studies of okra powdery mildew (Erysiphe cichoracearum) using bio-agents, plant extracts and chemical fungicides - KHALIKAR, P.V.; JAGTAP*, G.P.; SONTAKKE, P.L. (Indian Phytopathology, 2011)
Okra (Abelmoschus esculentus (L.) Moench occupies a prominent place in the horticultural wealth and economyÂ of the country. Powdery mildew disease on okra (Abelmoschus esculentus (L.) Moench incited by fungus, ErysipheÂ cichoracearum is a limiting factor in the successful cultivation in Marathwada region of Maharashtra State. Studies were carriedÂ out to find out disease management strategies against okra powdery mildew using bioagents, plant extracts and chemicalÂ fungicides. Disease incidence and severity declined only after third and fourth sprays. The fungicide Dinocap 46% EC (0.1 %)Â showed significantly lowest disease incidence (18.51 %) and disease severity (9.86 PDI) with maximum (84.09 %) diseaseÂ control. On the basis of effectiveness in controlling the powdery mildew disease of okra the most effective fungicidesÂ recorded in the order of merit were Dinocap 46% EC (0.1 %), Sulphur 80 WP (0.3 %) and Propiconazole 25 EC (0.1%). The fruitÂ yield (t/ha) ranged from 7.53 to 11.21 t/ha. Maximum fruit yield (11.21 t/ha) and highest per cent increase in yield (58.92 per cent)Â over unsprayed control was recorded in fungicide dinocap 46% EC sprays followed by sulphur 80 WP (0.3 %) and propiconazoleÂ 25 EC (0.1%) fungicides. Maximum test weight (60.80 g) and maximum increase in test weight (15.94 g) over unsprayed controlÂ was also found in fungicide dinocap 46% EC.